2019
DOI: 10.1016/j.jebo.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Embezzlement and guilt aversion

Abstract: Psychological game theory can contribute to renew the analysis of unethical behavior by providing insights on the nature of the moral costs of dishonesty. We investigate the moral costs of embezzlement in situations where donors need intermediaries to transfer their donations to recipients and where donations can be embezzled before they reach the recipients. We design a novel three-player Embezzlement Mini-Game to study whether intermediaries in the laboratory suffer from guilt aversion and whether guilt aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 70 publications
4
25
0
2
Order By: Relevance
“…Guilt aversion is an important factor of cooperation that lives up to the expectations of others, since people suffer from guilt if they disappoint others [10,11,12,13] (see Materials and Methods for a more detailed definition). Both laboratory and field experiments have supported this theory for populations in both the East and the West (e.g., East [14,15,16], West [11,17,18,19,20,21,22,23,24]).…”
Section: Introductionmentioning
confidence: 90%
“…Guilt aversion is an important factor of cooperation that lives up to the expectations of others, since people suffer from guilt if they disappoint others [10,11,12,13] (see Materials and Methods for a more detailed definition). Both laboratory and field experiments have supported this theory for populations in both the East and the West (e.g., East [14,15,16], West [11,17,18,19,20,21,22,23,24]).…”
Section: Introductionmentioning
confidence: 90%
“…Notably, many experimental studies have demonstrated that belief-dependent guilt is a predominant motivator for trustees in a trust game (for a broader discussion, see 19 ). Additionally, both laboratory and field experiments have supported guilt aversion theory for populations in both the East and West (e.g., East 20 22 ; West 11 , 17 , 18 , 23 30 ).…”
Section: Introductionmentioning
confidence: 92%
“…Podemos observar en la tabla 2 que la mayoría de los artículos centran sus esfuerzos en estudiar la culpa y la reciprocidad como generadoras de equilibrios no racionales. Los artículos etiquetados como "estudiar la culpa" examinan el papel de la culpa (Bracht y Regner, 2013;Giaccherini y Ponti, 2018), la aversión a la culpa (Attanasi et al, 2019;Bellemare et al, 2018;Charness y Dufwenberg, 2006) y cómo se utiliza la culpa para manipular las acciones de los demás (Cardella, 2016). Los artículos sobre reciprocidad investigan cómo la reciprocidad moldea el comportamiento, como Diekmann (2004) y Franzen y Pointner (2013), pero también cuando la reciprocidad no es tan importante, como Chen y Houser (2019).…”
Section: Preferencias Socialesunclassified